Fe-decorated all-boron B40 fullerene serving as a potential promising active catalyst for CO oxidation: A DFT mechanistic approach. (15th September 2020) - Hamadi, Hosein; Shakerzadeh, Ehsan; Esrafili, Mehdi D.
Graphical abstract: Highlights: Fe adsorption over B40 fullerene is investigated. Fe@B40 fullerene proposed as a highly active noble-metal free catalyst for carbon CO oxidation reaction. The CO oxidation reaction over Fe@B40 is controlled by termolecular Eley–Rideal (TER) mechanism. Abstract: In the present research, a special boron-based catalyst was introduced for carbon monoxide oxidation using dispersion-corrected DFT calculations. The iron metal is decorated at hexagonal and heptagonal rings of B40 fullerene, which is discovered as the first experimental boron allotrope in cage form. Accordingly, the Fe atom strongly chemisorbs on top of hexagonal and heptagonal rings of this fullerene. However, the adsorption energy for Fe atom above the hexagonal ring is found to be greater than that of over the heptagonal one. Thus, this complex selected as an appropriate catalyst for investigating the CO oxidation process. The conventional Eley–Rideal (ER), Langmuir–Hinshelwood (LH) and termolecular Eley–Rideal (TER) mechanisms were explored in detail. The outcomes have revealed that the acceptable mechanism for CO oxidation over Fe@B40 substrate is TER pathway. The results might be valuable for designing promising active boron-based catalyst for the CO oxidation.